Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.2106/00004623-200508000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome at a Minimum of Five Years After Reconstruction of the Anterior Cruciate Ligament

Abstract: Callison, J. Claiborne Jr.; Secic, Michelle; Fleisch, Sheryl B.; and Wright, Rick W., ,"Clinical outcome at a minimum of five years after reconstruction of the anterior cruciate ligament

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
66
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(77 citation statements)
references
References 36 publications
(24 reference statements)
3
66
0
4
Order By: Relevance
“…We evaluated the weight gain (divide 2 group: Gain more than 15 lb or not) after ACL reconstruction and analysed the correlation between weight increase and development of OA and found that there was significant correlation between weight increase and development of OA (Odds ratio: 5.690, p-value=0.025). These results were quite similar to a report by Spindler et al [1].…”
supporting
confidence: 93%
“…We evaluated the weight gain (divide 2 group: Gain more than 15 lb or not) after ACL reconstruction and analysed the correlation between weight increase and development of OA and found that there was significant correlation between weight increase and development of OA (Odds ratio: 5.690, p-value=0.025). These results were quite similar to a report by Spindler et al [1].…”
supporting
confidence: 93%
“…Overall, we observed that a higher BMI was associated with lower subjective IKDC scores at 1 and 2 months, but this effect did not necessarily occur when the traditional obesity threshold was used as a cutoff point (nonobese ¼ BMI ,30, obese ¼ BMI !30). The association between obesity and lower self-reported outcomes has been well documented in long-term studies, 21,49 but little is known about the effect of BMI on patient function during the early phases of recovery. Our results indicate that BMI had a direct association with patient-reported function as early as the first 2 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Female athletes have a greater risk than male athletes for rupturing the ACL 14 , and they are more likely to rupture the contralateral ACL after reconstruction 15 . Although large cohorts of patients have no sex-based difference in risk of recurrent ACL tears 14,16,17 , female soccer players have a higher risk of ACL reinjury compared with their male counterparts 18 . Thus, women may gain the most benefit from education to guide their expectations following ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%